Colorectal Cancer Metastases Settle in the Hepatic Microenvironment Through α5β1 Integrin. Issue 10 (October 2015) - Pelillo, Chiara; Bergamo, Alberta; Mollica, Hilaria; Bestagno, Marco; Sava, Gianni
ABSTRACT Colorectal cancer (CRC) metastasis dissemination to secondary sites represents the critical point for the patient's survival. The microenvironment is crucial to cancer progression, influencing tumour cell behaviour by modulating the expression and activation of molecules such as integrins, the cell‐extracellular matrix interacting proteins participating in different steps of the tumour metastatic process. In this work, we investigated the role of α5β1 integrin and how the microenvironment influences this adhesion molecule, in a model of colon cancer progression to the liver. The culture medium conditioned by the IHH hepatic cell line, and the extracellular matrix (ECM) proteins, modulate the activation of α5β1 integrin in the colon cancer cell line HCT‐116, and drives FAK phosphorylation during the process of cell adhesion to fibronectin, one of the main components of liver ECM. In these conditions, α5β1 modulates the expression/activity of another integrin, α2β1, involved in the cell adhesion to collagen I. These results suggest that α5β1 integrin holds a leading role in HCT‐116 colorectal cancer cells adhesion to the ECM through the modulation of the intracellular focal adhesion kinase FAK and the α2β1 integrin activity. The driving role of the tumour microenvironment on CRC dissemination, here detected, and described, strengthens and adds new value to the concept that α5β1 integrin can be an appropriate and relevant therapeutic target for the control of CRC metastases. J. Cell. Biochem. 116: 2385–2396, 2015. © 2015 Wiley Periodicals, Inc.